α‐synuclein oligomers and fibrils: a spectrum of species, a spectrum of toxicities - Alam, Parvez; Bousset, Luc; Melki, Ronald; Otzen, Daniel E. (Journal of neurochemistry, 2019)
This review article provides an overview of the different species that α‐synuclein aggregates can populate. It also attempts to reconcile conflicting views regarding the cytotoxic roles of oligomers versus fibrils. α‐synuclein, while highly dynamic in the monomeric state, can access a large number of different assembly states. Depending on assembly conditions, these states can interconvert over different timescales. The fibrillar state is the most thermodynamically favored due to the many stabilizing interactions formed between each monomeric unit, but different fibrillar types form at different rates. The end distribution is likely to reflect kinetic partitioning as much as thermodynamic equilibra. In addition, metastable oligomeric species, some of which are on‐pathway and others off‐pathway, can be populated for remarkably long periods of time. Chemical modifications (phosphorylation, oxidation, covalent links to ligands, etc.) perturb these physical interconversions and invariably destabilize the fibrillar state, leading to small prefibrillar assemblies which can coalesce into amorphous states. Both oligomeric and fibrillar species have been shown to be cytotoxic although firm conclusions require very careful evaluation of particle concentrations and is complicated by the great variety and heterogeneity of different experimentally observed states. The mechanistic relationship between oligomers and fibrils remains to be clarified, both in terms of assembly of oligomers into fibrils and potential dissolution of fibrils into oligomers. While oligomers are possibly implicated in the collapse of neuronal homeostasis, the fibrillar state(s) appears to be the most efficient at propagating itself both in vitro and in vivo, pointing to critical roles for multiple different aggregate species in the progression of Parkinson’s disease (https://onlinelibrary.wiley.com/page/journal/14714159/homepage/virtual_issues.htm). This article is part of the Special Issue “Synuclein”. This review discusses the roles of oligomers and fibrils in the molecular events underlying α‐synuclein (α‐syn) aggregation in an attempt to reconcile conflicting view on their roles in cytotoxicity. We start with a discussion of α‐syn dynamics, polymorphism, and kinetic partitioning between different aggregate species in vitro and in vivo. We provide an overview of different oligomeric species, including the co‐existence of on‐ and off‐pathway types of oligomers and the impact of chemical modifications on their formation and stabilities. Finally, we evaluate the role of oligomers and fibrils in the spread of pathology in Parkinson’s Disease, concluding that the mechanistic relationship between oligomers and fibrils still needs to be clarified and will likely remain a subject of intense investigation for some time. This article is part of the Special Issue “Synuclein”.